Effect of combined modality treatment on morphofunctional state of bronchial epithelium in lung cancer patients - A. Yu. Dobrodeev (Sibirskij Onkologičeskij Žurnal, 2016)
Effect of combined modality treatment on morphofunctional state of the bronchial epithelium of 29 patients with stage III lung cancer was studied. Neoadjuvant chemotherapy (paclitaxel/carboplatin) had no negative effect on the state of the bronchial epithelium. Surgery with intraoperative radiation therapy at a single dose of 10 Gy or 15 Gy with cisplatin radiosensitization caused mucosal damage as alteration, dystrophy and desqumation of the covering epithelium. The damaged epithelium was regenerated due to the reserved cells coming from the damaged margins with the formation of an epidermoid regenerative layer and subsequent cell differentiation. In a year after treatment, the bronchial mucosa was covered by the multinuclear cylindrical epithelium and moderate sclerosis occurred in the stroma